Self-Declared Physical Activity Levels and Self-Reported Physical Fitness in a Sample of Italian Adolescents during the COVID-19 Pandemic - Alessandro Gatti; Lorenzo Pugliese; Vittoria Carnevale Pellino; Marco Del Bianco; Matteo Vandoni; Nicola Lovecchio (MDPI AG, 2022)
Only 20% of children worldwide reach the suggested physical activity (PA) levels, and the COVID-19 restrictions seemed to have worsened this situation. In addition, physical fitness (PF) is a crucial marker of health and combined with PA could predict future health status. The aim of this study was to compare reported PA and PF levels in a sample of Italian adolescents. We administered the International PA Questionnaire and International Fitness Enjoyment Scale to 208 adolescents aged 16.0 ± 1.5 (N = 166 females, 16 ± 2.0 years) recruited from a high school in the province of Milan (Italy). The majority of the subjects were "Minimally active" but reported adequate PF levels. In particular, subjects who reported a "Very good" PF perception, had a lower PA level. The misperception of reported PA and PF from our sample could reduce the future PA level in adolescents and lead to a negative spiral of disengagement in PA. These findings should lead to more attention on and improvements to PA promotion in the adolescent population after the restrictions caused by the COVID-19 pandemic.